Antibiotic Resistance of Enterococci Isolated from Healthy Humans and Patients with Various Pathologies - M. V. Sycheva; O. L. Kartashova; N. E. Shchepitova; Al. A. Safronov (Антибиотики и Химиотерапия, 2020)
High resistance of enterococci to the currently used antibacterials, such as tetracycline, ciprofloxacin and ampicillin was observed. Streptomycin, gentamicin and vancomycin showed the highest activity against the clinical isolates of Enterococcus spp. Streptomycin and gentamicin showed the highest activity against the intestinal enterococci. The PCR revealed the presence of the genetic determinants of resistance to aminoglycosides, glycopeptides and tetracycline in the isolates. The comparison of the results of the bacteriological and genetic tests provided detection of fecal and clinical isolates of Enterococcus spp. possessing the genes of resistance to aminoglycosides and glycopeptides, still without the finally developed significant clinical resistance to the above antibacterials.